2007
DOI: 10.1136/gut.2005.089508
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of symptom pattern in idiopathic severely delayed gastric emptying: gastric emptying rate or proximal stomach dysfunction?

Abstract: Background: Idiopathic gastroparesis is a syndrome characterised by severely delayed gastric emptying of solids without an obvious underlying organic cause. Although delayed gastric emptying is traditionally considered the mechanism underlying the symptoms in these patients, poor correlations with symptom severity have been reported. Aims: To investigate proximal stomach function and to study the correlation of delayed gastric emptying and proximal stomach dysfunction with symptom pattern and severity in idiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
136
4
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(149 citation statements)
references
References 30 publications
6
136
4
3
Order By: Relevance
“…Treatment options for FD and gastroparesis are very limited. Although prokinetics stimulate peristalsis and improve gastric pump functions by enhancing antral contractility, electrical rhythm, and/or antroduodenal coordination, sometimes they do not result in significant symptom improvement (27,34). This is because patients with delayed gastric emptying often have impaired gastric accommodation and/or visceral hypersensitivity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Treatment options for FD and gastroparesis are very limited. Although prokinetics stimulate peristalsis and improve gastric pump functions by enhancing antral contractility, electrical rhythm, and/or antroduodenal coordination, sometimes they do not result in significant symptom improvement (27,34). This is because patients with delayed gastric emptying often have impaired gastric accommodation and/or visceral hypersensitivity.…”
Section: Discussionmentioning
confidence: 98%
“…Prokinetics are the first-line medicine for treating delayed gastric emptying. However, there is a poor correlation between the acceleration of gastric emptying and the improvement of gastric symptoms with prokinetics (27).…”
mentioning
confidence: 99%
“…Correlations were also found between visceral hypersensitivity of the proximal stomach to mechanical distension and epigastric pain, early satiety and weight loss. 24 The study concluded that the pattern of functional dyspepsia symptoms was determined by sensitivity and accommodation of the proximal stomach, rather than by the severity of delayed gastric emptying. 24 Inconsistencies among previous studies 6,8,17,24 might be due to differences in Delayed proximal GE…”
Section: Discussionmentioning
confidence: 99%
“…6,8,17,24,26 Few studies have dealt with the relationship between gastric solid emptying of the proximal stomach and symptoms. In a study that compared food distribution in the stomachs of healthy subjects and patients with functional dyspepsia, postprandial fullness was found to be related to food retention in the proximal stomach late after meal ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…Routine GE imaging can be used to measure both regional and total GE. Visual inspection of fundal and antral GE and quantification of regional emptying with fundic and antral regions of interest can be helpful for defining abnormal physiology and explaining dyspeptic symptoms, especially when global GE values are normal (56)(57)(58)(59). Studies have shown an association between symptoms of nausea, early satiety, abdominal distention, and acid reflux and proximal gastric retention; whereas vomiting is associated more with delayed distal GE (57).…”
Section: Assessment Of Proximal and Distal Gastric Functionmentioning
confidence: 99%